Talent detection and development in alpine skiing - Raschner, C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The presentation will provide an overview of Austrian`s talent detection, development and selection programs in ski racing with the following topics: • How coaches perceive and select potential talent in ski racing, • Physical maturity of youth ski racers and the relative age effect, • The significance of ski boarding schools in talent detection and development, • Age-specific demand profiles in ski racing, • The role of systematic fitness testing from early age to monitor athletes` strengths and weaknesses, • Essential age and gender-specific components of longitudinal fitness testing in ski racing, • Developmental training programs for youth ski racers to increase performance and reduce injury risk.